Uniparental maternal tetrasomy X co-occurrence with paternal nondisjunction: investigation of the origin of 48,XXXX - Keiko Shimojima Yamamoto; Sakurako Yamamoto; Taichi Imaizumi; Satoko Kumada; Toshiyuki Yamamoto (Human Genome Variation)
Abstract Tetrasomy X or 48,XXXX is a rare sex chromosome aneuploidy. The parental origin of tetrasomy X in a female patient with developmental delay was analyzed; all four X chromosomes were derived from the mother, and there were no paternally derived sex chromosomes. This finding indicates a rare incidental co-occurrence of maternal and paternal nondisjunction or polysomy rescue. The mechanism of 48,XXYY, which is related to developmental delay in males, was analyzed for comparison.